Low-dose radiation treatment enhances systemic antitumor immune responses by overcoming the inhibitory stroma. Issue 2 (26th October 2020) - Barsoumian, Hampartsoum B; Ramapriyan, Rishab; Younes, Ahmed I; Caetano, Mauricio S; Menon, Hari; Comeaux, Nathan I; Cushman, Taylor R; Schoenhals, Jonathan E; Cadena, Alexandra P; Reilly, Timothy P; Chen, Dawei; Masrorpour, Fatemeh; et al.
Abstract : Background: Despite some successes with checkpoint inhibitors for treating cancer, most patients remain refractory to treatment, possibly due to the inhibitory nature of the tumor stroma that impedes the function and entry of effector cells. We devised a new technique of combining immunotherapy with radiotherapy (XRT), more specifically low-dose XRT, to overcome the stroma and maximize systemic outcomes. Methods: We bilaterally established 344SQ lung adenocarcinoma tumors in 129Sv/Ev mice. Primary and secondary tumors were irradiated with either high-dose or low-dose of XRT with systemic anti-programmed cell death protein 1 and anti-cytotoxic T-lymphocyte associated protein 4 administration. Survival and tumor growth were monitored for the various groups, and secondary tumors were phenotyped by flow cytometry for immune populations. Tumor growth factor-beta (TGF-β) cytokine levels were assessed locally after low-dose XRT, and specific immune-cell depletion experiments were conducted to identify the major contributors to the observed systemic antitumor effect. Results: Through our preclinical and clinical studies, we observed that when tumor burden was high, there was a necessity of combining high-dose XRT to 'prime' T cells at the primary tumor site, with low-dose XRT directed to secondary (metastatic) tumors to 'modulate the stroma'. Low-dose XRT improved the antitumor outcomes of checkpoint inhibitors by favoring M1 macrophage polarization, enhancing natural killer (NK) cell infiltration, and reducing TGF-β levels. Depletion of CD4 + T cells and NK cells abrogated the observed antitumor effect. Conclusion: Our data extend the benefits of low-dose XRT to reprogram the tumor environment and improve the infiltration and function of effector immune cells into secondary tumors.